ANALYSIS OF FACTORS AFFECTING THE PRODUCTION AND INCOME OF RICE FARMING IN RAINFED RICE FIELDS IN BINAGA KARAENG VILLAGE, LEMBANG KABUPATEN PINRANG - Ikrawati, Ikra wati (Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study aims to determine the factors that affect rice farming in rainfed rice fields in Binanga Karaeng Village, Lembang District, Pinrang Regency. The sampling method was purposive or intentionally, the population in this study were 120 rainfed rice farmers. the sampling technique in this study was the Simple Random Sampling technique so that 36 respondents were obtained from 30% of rice farmers in rainfed rice fields in Binanga Karaeng Village, Lembang District, Pinrang Regency. The results showed that rice farming production in rainfed paddy fields in Binanga Karaeng Village, Lembang Subdistrict, Pinrang Regency amounted to 4,098 kg/ha per growing season, while the income generated was Rp 24,642.33 ha per growing season. Factors that affect rice farming in rainfed rice fields simultaneously are land area, seeds, fertilizers, pesticides, and labor. While the farm production factors that affect persial are land area, seeds, fertilizers, and pesticides. If the land area increases by 1% then farm production will increase by 0.535%, if rice seeds are added by 1% then farm production will increase by 0.817%, for fertilizer if added by 1% then production increases by 0.409%. While pesticides if added 1% of users then production will actually decrease by 0.852%.